(untitled) (Tempo e Argumento, 2011)
This article tries to bring to light some obscure aspects of two events that marked the Brazilian Republic in the beginning of the twentieth century: the Revolt of the Vaccine (1904) and Revolt of Sailors (1910). Some of these aspects are related to the exile, which were used as punishment by the Brazilian State after the end of those two events that occurred in Rio de Janeiro. What remains unclear is why these men and women were condemned to exile and who led the Brazilian state to send them to the Territory of Acre, in the Amazon. Therefore, it is aimed to set within the standards and legal frameworks adopted at the time the intentions and meanings of such measures, discussing also the meanings of perceptions of imposed punishments on the displaced people in terms of republican order, and the purpose - symbolic and practical - of sending these people away to the "confines" of the Amazon, in Acre.